Mieczysław Kotlarczyk – a Teacher and Artistic Friend of John Paul II - Cecylia Kuta (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
Mieczysław Kotlarczyk played an important role in the life of Pope John Paul II. The spiritual bond between friends born in the same city exerted a significant impact on both their lives and work. And yet it remains unknown to the public, just as Kotlarczyk himself. Raised in a theatre-related family, Kotlarczyk remained affiliated with the theatre throughout his life. This paper presents his life path and the fate of the Rhapsodic Theatre, which Kotlarczyk was managing from 1941, and which operated under the auspices of the “Unia” (“Union”) underground organization. After World War II, despite reprisals from the communist authorities and the subordination to thesecret service, Kotlarczyk tried to continue his activity. In 1953, the Rhapsodic Theatre was liquidated by the authorities. Even though in 1957, as part of the so-called thaw, there was a consent to reactivate the theatre, ten years later however, it was definitely shut down. Among those protesting against the decision, was Karol Wojtyła, the then Archbishop of Kraków.